Manipulating Word Representations, and Preparing Students for Coding Jobs? - Hill, Robin K.; Guzdial, Mark (Communications of the ACM, 2017)
The article discusses natural language processing and the teaching of computer programming in public schools. Topics include the computer program word2vec's ability to give manipulations of word representations that resemble semantics produced by vector math, and educational historian Larry Cuban's argument that computer programming education advocates blending the roles of school in preparing citizens and preparing workers as computing is necessary in society.